Vitamin D and/or calcium to prevent fractures and falls: protocol for a systematic review and meta-analysis - David Williamson; Olivier Massé; Claudia Mei Mercurio; Sébastien Dupuis; Alexandra Arruda; Katherine Desforges; Nicolas Dugré; Gabriel Dallaire (BMJ Open)
Background Previous systematic reviews on fracture and fall prevention have generally shown no efficacy with calcium or vitamin D alone and conflicting findings with that of vitamin D combined with calcium. Despite these findings, increases in vitamin D and calcium prescriptions have been reported in many countries, as many clinicians, guidelines and regulatory agencies still largely recommend universal supplementation to adults.Methods and analysis We will conduct a systematic review of randomised controlled trials on the efficacy of vitamin D and/or calcium in fracture and fall prevention. A systematic search will be performed in Medline, Embase, CENTRAL, International Clinical Trials Registry Platform and Clinicaltrials.gov (1 January 2024). We will also hand search abstracts published in relevant congress and journals (2021–2023) and the reference lists of included trials. We will consider any trial involving the pharmacological administration of calcium alone, vitamin D alone or vitamin D combined with calcium against placebo or no treatment in adults. The primary outcome will be the number of participants with fractures at any site. The secondary outcomes will be the number of participants with hip fractures, non-vertebral fractures, vertebral fractures and falls, and the rate of falls. Two reviewers will independently screen and include the trials, extract the data and assess the risk of bias using the second version of the Cochrane risk-of-bias tool. We plan to pool outcomes to conduct random-effects meta-analyses and to appraise the certainty of evidence using Grading of Recommendations Assessment, Development and Evaluation (GRADE). Many prespecified subgroup and sensitivity analyses will be performed to explore the potential heterogeneity and to test the robustness of our findings.Ethics and dissemination This systematic review does not require research ethics approval. The results will be disseminated in peer-reviewed journals and help inform clinicians, guidelines and regulatory agencies.PROSPERO registration number CRD42023483915